Niaodukang for the treatment of chronic kidney disease: Regulation of the TRAF3/NF-κB2 signaling pathway and its improvement of the intestinal barrier - Juan Xu; Lei Wang; Hong Wang; Jie Pang; Linna Liu; Ting Zhang; Ling Yuan; Xiaoxue Cui; Qian Jiang; Yanlin Li (Tissue and Cell, 2026)

Comparative transcriptome analysis of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) and Epinephelus fuscoguttatus under temperature stress - Pengfei Duan; Yongsheng Tian; Zhentong Li; Shuai Chen; Linlin Li; Xinyi Wang; Linna Wang; Yang Liu; Jieming Zhai; Wensheng Li; Qingbin Wang; Wenhui Ma; et al. (Aquaculture, 2024)

Effects of water–nitrogen coupling on soil water and nitrogen, photosynthesis, yield and water use of lettuce under different application rates of poly‐γ‐glutamic acid - Lu Liu; Wenjuan Shi; Linna Pang (Irrigation and Drainage, 2023)
As an environmentally friendly, super water‐absorbable agent and fertilizer synergist, the influences of poly‐γ‐glutamic acid (γ‐PGA) on soil N and crop photosynthesis are still not well understood. A pot experiment was conducted to evaluate the effects of water–nitrogen coupling on soil water and nitrogen content, photosynthesis, yield and irrigation water use efficiency (IWUE) of lettuce under different γ‐PGA application rates. In this study, there were three factors and four levels: γ‐PGA with four application levels of 0, 1, 2 and 4 g kg −1 ; the rates of urea were 0, 0.2, 0.4 and 0.6 g kg −1 ; and the irrigation amounts were 40%, 60%, 80% and 100% of the lettuce water requirement (ET c ). The results showed that within 8 days after sowing, the soil water and nitrogen (NO 3 − ‐N and NH 4 + ‐N) content increased with increasing γ‐PGA application rates. The amount of irrigation water and nitrogen application had an effect on IWUE, net photosynthetic rate ( P n ) and stomatal conductance ( G s ). Lettuce yield was significantly correlated with P n , G s and intercellular CO 2 concentration ( C i ) by path analysis. Moreover, the P2N2W3 treatment (γ‐PGA 2 g kg −1 , nitrogen 0.2 g kg −1 and 80% ET c ) was the most suitable treatment to obtain the highest lettuce yield and IWUE.

The complete mitochondrial genome of the hybrid grouper Epinephelus moara (♀)×Epinephelus tukula (♂), and phylogenetic analysis in subfamily Epinephelinae - Zhentong Li; Yongsheng Tian; Meiling Cheng; Linna Wang; Jingjing Zhang; Yuping Wu; Zunfang Pang; Wenhui Ma; Jieming Zhai (Acta Oceanologica Sinica, 2020)